Facial paralysis associated to hypothyroidism in a dog - Romao, Felipe Gazza [UNESP]; Poci Palumbo, Mariana Isa [UNESP]; Oshika, Josyanne Christine [UNESP]; Machado, Luiz Henrique de Araújo [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The hypothyroidism is the most commonly endocrinopathy in dogs, that occurs preferentially in middle-aged pure breed. The clinical signs associated with hypothyroidism are variable, many times non-specific, including metabolical, dermatological or cardiovascular. The main laboratorial findings are non-regenerative anemia and hypercholesterolemia. Hyponatremia, increase on alanine transferase and alkaline phosphatase activity also can be observed in a lower frequency. There are some reports of peripheral neuropathies caused by hypothyroidism, but the pathophysiology of this process is still unknown. There are specific diagnostic tests that can be used to help diagnose hypothyroidism, and those should be aligned together with the animal's clinical symptoms. The thyroxine stimulating hormone, and free and total thyroxine concentrations are the most used tests. A Pit Bull dog, female, over weighted, was treated presenting left facial paralysis. Thyroid function tests confirmed hypothyroidism. The animal was treated with hormonal replacement and there was improvement in clinical signs in 40 days, confirming that hypothyroidism was facial paralysis' cause.
Keywords: Hypothyroidism; obesity; facial paralysis; thyroxine